Digital Methods of Working time Management in a Flexible Labor Market - Charnavalau, Aliaksandr Viktor; Kuźmicki, Marek Grzegorz; Charnavalava, Zanna Vasylij (Economic and Regional Studies / Studia Ekonomiczne i Regionalne, 2022)
Working time management has become particularly relevant by mid-20th century. It has now become one of the top areas of interest for scientists who conduct research on management. This study is designed to review and evaluate selected new forms of work organization in the reality of today’s digital economy. This research was based on literature review covering scientific publications exploring working time management and forms of work organization in the digital economy. A descriptive method was used. The latest information technologies, computerization and digitization, the use of mobile devices and smartphones, and advanced geolocation technologies add a new dimension to the modern types and methods of working time management. The development of the digital economy accelerates and drives the transformation of the labor market, promoting the uptake of flexible employment systems, which produces multiple types of remuneration and working time systems, and leads to a variety of forms of employment contracts and their reduced duration. Digital technology creates a virtual labor market which is dominated by informal and flexible forms of employment based on outsourcing programs, individual orders, and fixed deadlines with are not accompanied by any regulations of the contractor’s working time. Under these conditions, flexibility and multifunctionality, and the ability to adapt to changing conditions are the key features that make a particular employee competitive.